Paradigma Pemasaran Pendidikan Pesantren: Mengintegrasikan Pendekatan Digital Untuk Mengubah Perilaku Pencarian Informasi Calon Siswa - Uut Mujiyati; Siti Aimah (Journal on Education, 2025)
The purpose of this research is to provide the implications and paradigms of Islamic marketing by incorporating a digital approach. The object of this research is the Islamic educational institute at MAS Al-Kamaliyah jeri which operates in the village of Manggoli, North Maluku. The methods in this research concern new trends in education heating management using qualitative research methods with case studies approaches. Data collection techniques in this study include observations, interviews and documentation. Observations were conducted by observing live activities and interactions in the school environment, including promotional events, teaching learning activities, and interaction between the school and the surrounding community. In-depth interviews were performed with the head of the school, marketing staff, teachers, students, parents of students, and surrounding communities to dig their experiences, views, and perceptions related to the Islamic education marketing paradigm. Based on data on the ground, the use of social media as the main channel became the paradigm of Islamic education marketing Students are increasingly relying on social media such as Instagram, Facebook, and TikTok to find information about Islamic educational institutions. It shows a shift from traditional media to digital platforms in the search for educational information. SocialMedia Offers Visual and Interactive Content Platforms like Instagram, Facebook, and TikTok enable educational institutions for more interesting and informative visual, video, and interactive content. This content can provide a clearer picture of the activities in the educational institutions.